2013
DOI: 10.1016/j.ydbio.2013.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Notch-signalling is required for head regeneration and tentacle patterning in Hydra

Abstract: Local self-activation and long ranging inhibition provide a mechanism for setting up organising regions as signalling centres for the development of structures in the surrounding tissue. The adult hydra hypostome functions as head organiser. After hydra head removal it is newly formed and complete heads can be regenerated. The molecular components of this organising region involve Wnt-signalling and β-catenin. However, it is not known how correct patterning of hypostome and tentacles are achieved in the hydra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 42 publications
13
62
0
Order By: Relevance
“…In the adult polyp, Notch was expressed in the body column, excluding the most aboral section, and at the base of the tentacles (Fig 1B). This expression pattern is similar to HyNotch expression in Hydra (Münder et al, 2013; Wenger et al, 2016). We also found that Notch is alternatively spliced to generate two main isoforms that share all major Notch domains and differ only in the first two exons, which encode EGF repeats (Fig.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In the adult polyp, Notch was expressed in the body column, excluding the most aboral section, and at the base of the tentacles (Fig 1B). This expression pattern is similar to HyNotch expression in Hydra (Münder et al, 2013; Wenger et al, 2016). We also found that Notch is alternatively spliced to generate two main isoforms that share all major Notch domains and differ only in the first two exons, which encode EGF repeats (Fig.…”
Section: Resultssupporting
confidence: 71%
“…DAPT treatment during regeneration led to a block in tentacle formation (Fig. 4A and B), a phenotype also known from other cnidarians (DuBuc et al, 2014; Fritz et al, 2013; Marlow et al, 2012; Münder et al, 2013). However, as shown above, the acetylated tubulin positive oral nervous system in regenerating, Notch inhibited polyps was normal (Fig 3B).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Cnidarians do not have a centralized nervous system but possess neural cells. In the evolutionarily derived Hydra , a proper Delta gene is missing and the small Notch receptor found in this species is involved in head and tentacle patterning [72]. In Nematostella (a sea anemone), a proper Notch protein and a short Delta ligand are present.…”
Section: Discussionmentioning
confidence: 99%
“…6 A-D). There also might be a link with Notch-signalling, which is important for both boundaries in Hydra (Münder et al, 2010;Münder et al, 2013).…”
Section: A Eph Receptors and Ephrins In Hydra 763mentioning
confidence: 99%